Ubiquitin‐Specific Protease 4 Is an Endogenous Negative Regulator of Metabolic Dysfunctions in Nonalcoholic Fatty Liver Disease in Mice. Issue 3 (15th September 2018) - Zhao, Yichao; Wang, Fang; Gao, Lingchen; Xu, Longwei; Tong, Renyang; Lin, Nan; Su, Yuanyuan; Yan, Yang; Gao, Yu; He, Jie; Kong, Lingcong; Yuan, Ancai; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD), characterized by hepatic steatosis (HS), insulin resistance (IR), and inflammation, poses a high risk of cardiometabolic disorders. Ubiquitin specific protease 4 (USP4), a deubiquitinating enzyme, is pivotally involved in regulating multiple inflammatory pathways; however, the role of USP4 in NAFLD is unknown. Here, we report that USP4 expression was dramatically down‐regulated in livers from NAFLD patients and different NAFLD mouse models induced by high‐fat diet (HFD) or genetic deficiency ( ob/ob ) as well as in palmitate‐treated hepatocytes. Hepatocyte‐specific USP4 depletion exacerbated HS, IR, and inflammatory response in HFD‐induced NAFLD mice. Conversely, hepatic USP4 overexpression notably alleviated the pathological alterations in two different NAFLD models. Mechanistically, hepatocyte USP4 directly bound to and deubiquitinated transforming growth factor‐β activated kinase 1 (TAK1), leading to a suppression of the activation of downstream nuclear factor kappa B (NF‐κB) and c‐Jun N‐terminal kinase (JNK) cascades, which, in turn, reversed the disruption of insulin receptor substrate/protein kinase B/glycogen synthase kinase 3 beta (IRS‐AKT‐GSK3β) signaling. In addition, USP4‐TAK1 interaction and subsequent TAK1 deubiquitination were required for amelioration of metabolic dysfunctions. Conclusion: Collectively, the present study provides evidence that USP4 functions as a pivotal suppressor in NAFLD and related metabolic disorders. (Hepatology 2018; 00:000‐000).